In Focus Maqāsid Al-Sharīʿah And Ijtihād As Instruments Of Civilisational Renewal: A Methodological Perspective - Kamali, Mohammad Hashim; Eriouiche , Mohammed; Mohadi, Mawloud (Journal of Contemporary Maqasid Studies, 2024)
This article develops the idea of a maqāsid-based framework for civilisational renewal (tajdīd hadārī), a broad and engaging prospect that also involves a review and reappraisal of the methodology of Islamic jurisprudence relating to the maqāsid. The author argues that this would enable Muslims to widen the scope and horizon of the maqāsid or objectives of Islamic law from their currently legalistic leanings towards the wider perspective of civilisational renaissance.